Omega-6 fatty acids: opposing associations with risk : the Ludwigshafen Risk and Cardiovascular Health Study - Delgado Gonzales de Kleber, Graciela; März, Winfried; Kleber, Marcus E. (Journal of clinical lipidology, 2017)
Background: Omega-6 polyunsaturated fatty acids (omega-6 PUFA) are recommended in European cardiovascular prevention guidelines. However, individual fatty acids have distinct biological functions, and there have been conflicting reports about the association of omega-6 PUFA with cardiovascular risk. Objective: The aim of our study was to investigate the association of individual omega-6 fatty acids with mortality in a cohort of patients referred for coronary angiography. Methods: Omega-6 PUFA proportions were measured in erythrocytes at baseline in a total of 3259 patients participating in the Ludwigshafen Risk and Cardiovascular Health Study using the HS-Omega-3 Index method. Associations of omega-6 PUFA with mortality were analyzed by Cox regression with adjustment for conventional risk factors. Results: During a median follow-up of 10.0 years, 975 patients (29.9%) died, 614 patients (18.8%) from cardiovascular causes. γ-Linolenic acid was inversely associated with all-cause and cardiovascular mortalities in models adjusted for cardiovascular risk factors with hazard ratios of 0.88 (0.82-0.95) and 0.86 (0.79-0.95) per 1-standard deviation increase, respectively. Adrenic acid and docosapentaenoic acid ω-6 were both directly associated with risk with hazard ratio of 1.10 (1.30-1.18) and 1.12 (1.05-1.19) for all-cause mortality, respectively. No association was found for arachidonic acid. Conclusions: We observed opposing associations of individual omega-6 PUFA with mortality risk. While LA and γ-linolenic acid were associated with reduced risk, there was a direct association for adrenic acid and docosapentaenoic acid. These differences do not support the use of omega-6 PUFA concentrations as a single combined metric, and the prognostic value of each individual member should be examined separately.